2018
DOI: 10.18290/rpsych.2018.21.4-4
|View full text |Cite
|
Sign up to set email alerts
|

The Free Will and Determinism Plus (FAD–Plus) scale: The validity and reliability of the Polish adaptation

Abstract: The article presents an analysis of the validity and reliability of the FAD-Plus scale by D. L. Paulhus and J. M. Carey, which is used to measure beliefs in free will, determinism, and the unpredictability of events. The results of three studies are presented. Based on the results of the first study, it was found that the tool has a consistent structure and that its 3-factor 16-item version is reliable. The second study revealed positive correlations between determinism and religious fundamentalism and belief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Furthermore, we foresee several applications for the FAD-Plus-I in the community. Specifically, individuals who believe in free will are more likely to hold healthy relationships with themselves and the others, and as argued by Feltz (2015), and believing in free will may be "necessary for autonomy, creativity, desert, reactive attitudes, dignity, love, and friendship" (p. 113), even be required to avoid interpersonal conflicts (Kane, 1996). For this reason, effective prevention and intervention strategies in the social context may benefit from considering the assessment of BFW, BFD, BSD, and BUP by means of the FAD-Plus-I, providing researchers and practitioners with a reliable and valid screening tool to assess and potentially support those at higher risk for displaying dysfunctional patterns of interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we foresee several applications for the FAD-Plus-I in the community. Specifically, individuals who believe in free will are more likely to hold healthy relationships with themselves and the others, and as argued by Feltz (2015), and believing in free will may be "necessary for autonomy, creativity, desert, reactive attitudes, dignity, love, and friendship" (p. 113), even be required to avoid interpersonal conflicts (Kane, 1996). For this reason, effective prevention and intervention strategies in the social context may benefit from considering the assessment of BFW, BFD, BSD, and BUP by means of the FAD-Plus-I, providing researchers and practitioners with a reliable and valid screening tool to assess and potentially support those at higher risk for displaying dysfunctional patterns of interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Методика FAD-Plus была адаптирована в ряде стран. Авторы польской адаптации (Kondratowicz-Nowak et al, 2018) использовали версию с 16 пунктами, объединив субшкалы фаталистического и научного детерминизма в единый фактор детерминизма. Серия исследований показала положительные корреляции веры в детерминизм с религиозным фундаментализмом и верой в несправедливый мир, а также ряд закономерностей, связанных с эмоциональными переживаниями, в частности, положительные корреляции веры в свободу воли с позитивными эмоциями, отрицательные корреляции веры в детерминизм с позитивными эмоциями и удовлетворенностью жизнью.…”
Section: вера в свободу/детерминизм как объект психологической диагностикиunclassified
“…The subscale “unpredictability” assesses non-deterministic worldviews, the degree to which individuals believe that all events are not completely determined by previously existing causes. The FAD-Plus has been widely used by the free will belief researchers, and also translated into French (Caspar et al, 2017 ), Polish (Kondratowicz-Nowak et al, 2018 ), and Chinese (Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the wordings of the two translations are different, the possibility of translation-related artifacts in the scoring processes cannot be ruled out. As an example of how translation can change the factorial structure of the FAD-Plus, Kondratowicz-Nowak et al ( 2018 ) assumed the Polish-translated FAD-plus as a scale consisting of three factors. Although both of the two Japanese-translated scales have been validated to assess the four factors, Watanabe et al ( 2014 ) removed some items during the validation process of the FAD+ and reported the full-item version as reference information without detailed results “for use in international comparisons.” Thus, a direct comparison of the psychometric properties of these two translations is necessary to consider whether the scores assessed by them can be interpreted interchangeably.…”
Section: Introductionmentioning
confidence: 99%